COMPARISON OF TWO DIFFERENT MULTIPLEX SYSTEMS IN CALCULATING KINSHIP AMONG CLOSE RELATIVES - Mirjana Beribaka; Selma Hafizović; Amela Pilav; Mirela Džehverović; Damir Marjanović; Jasmina Čakar (Genetics & Applications, 2017)
This study compares the results obtained using two multiplex systems, PowerPlex® 16 System and PowerPlex® Fusion System, to evaluate the probability of a specific kinship relationship between the offspring of three pairs of identical twins, such as full kinship (siblings), first-degree relatives (first cousins) and half-siblings. Genomic DNA was isolated and amplified from buccal swab and selected short tandem repeat (STR) markers were detected. Electropherograms were generated and analyzed for all persons, using two multiplex systems. Paternity testing for every nine offspring of six examined couples was performed and in all cases the probability that the alleged father is the true father, was over 99.9999%. Kinship analyses were performed setting up two different hypotheses and calculating the likelihood ratio (LR) and kinship probability. Determining the degree of kinship between persons who were full siblings, likelihood ratio showed the highest values contrary to other two types of kinship. Kinship analyses between first cousins showed a higher probability that the examined persons are half-siblings, rather than they are first cousins. In most cases, the introduction of additional seven loci included in PowerPlex® Fusion System increased the values of average likelihood ratios. It is recommendable to use over 20 STR loci in complex kinship analyses.